The Forgotten Translators of Ancient Greek Tragedies - Bibik, Barbara (Porównania, 2020)
There is an ample number of Polish renditions of ancient Greek tragedies. Unfortunately, only a few names of those Polish translators are commonly known. The rest, written especially in the 19th century, is still waiting for someone to be interested in their works. Therefore, in my paper I would like to focus on the unrecognized translators from this century. They are widely forgotten today, yet they did great work at the time to acquaint the Polish public with Greek tragedies. My aim is also to recognize the tragedies they chose to translate which often seem not to be an obvious choice.